Innovations in sustainable agriculture: case study of Lis Valley irrigation district, Portugal - Oliveira, Maria de Fátima (2019)
The innovation of agricultural systems management is a determinant factor that guarantees adaptation to a new paradigm of global economy, environmental protection, and social requirements. The conventional concepts of innovation, applicable to new products and processes, do not consider many characteristics of the agricultural sector, such as social innovation and innovation resulting from new or renewed processes. Nevertheless, the overall impact of innovation on yields, competitiveness, and value can be hampered by the limited understanding or misinterpretation of Agriculture Innovation paradigms. For instance, the Rural Development Program (RDP) applies a restrict concept of innovation, being unable to embrace the full range of activities intended to implement new practices within the framework of the Agricultural Knowledge and Innovation System (AKIS). Stimulating innovation in agriculture demands a change in policy innovation of RDP in order to preserve natural resources and combine agricultural priorities and the rural environment with the concepts of innovation. This paper focuses on the different views of the concept of innovation within the Program of Operational Groups (OGs) of the European Innovation Partnership for Agricultural Productivity and Sustainability (EIP-AGRI), analyzing the Portuguese case study of the Lis Valley Irrigation District whose main innovation objective was to achieve and implement new processes of water management aiming at the conservation of natural resources as well as sustainable social and economic agricultural development. The Portuguese experience highlights why the application of innovation in agriculture may not reach the desirable outcomes